Technology development of fatty acids obtaining from soapstok using saponification - Natalia Sytnik (PC Technology Center, 2021)
The processing of oil refining waste is essential from economic and environmental points of view. An important issue is the processing of soapstock to extract fatty acids, which are raw materials for various industries.